Effect of Market Conditions, Oversubscription and Market Efficiency on IPO Underpricing - Gupta, Kanika (Indian Journal of Finance, 2011)
The purpose of this paper is to examine the initial price performance of recent Indian IPOs. For this purpose, the study has been divided in two parts: one year before Feb 2008 represents the "bubble" phase - when sensex moves from around 12,000 to 18,000&one year after 2008, represents "slump" when sensex fall from around 18,000 to 9,000 and the IPO listed on Bombay Stock Exchange during each of the time periods have been tested on four parameters to find if the IPOs are under priced. The first one is to examine the unadjusted under pricing and second is to see the impact of market conditions on under pricing. The Third parameter is to evaluate the efficiency of the market and fourth is to see the impact of over subscription on under pricing of the issues. The sample consists of 103 new issues for year 07-08 and 29 new issues for the year 08-09. The results shows that sufficient under pricing exists for the new issues in the year 07-08 and also, it is positively affected by over subscription and market conditions, but the market is not efficient enough for the year as no correction has been made by the end of the listing day in under pricing scenario. Whereas, the year 08-09, shows little signs of under pricing, instead most of the issues are over priced. It also does not show any relation of under pricing with market conditions or over subscription. Hence, the issues in this year follow a random walk and there is uncertainty in the market.